Total Synthesis of (–)-Alstofolinine A: Selected Furan Oxidation/ Cyclization Cascade - Zhang, Ye; Zhang, Lei; Qi, Xiangbing (Synlett, 2020)
Indole-fused tetracyclic ring systems containing nitrogen atoms are common core skeletons of many indole alkaloids such as sarpagine, macroline, and ajmaline. Efficient and stereoselective construction of these ring systems can promote the development of the corresponding alkaloid syntheses. In this article, we briefly summarize our current progress toward the application of the aza-Achmatowicz reaction and indole nucleophilic addition reaction cascade for the first asymmetric total synthesis of the macroline-type indole alkaloid (–)-Alstofolinine A. Our synthetic strategy is based on furan oxidation/rearrangement and proceeds from easily accessible materials such as indole and furan derivatives.
Keywords: aza-Achmatowicz rearrangement; furan; indole; natural product synthesis; selective oxidation